Asymptomatic bradycardia amongst endurance athletes - Doyen, B.; Matelot, D.; Carré, F. (The Physician and Sportsmedicine, 2019)
It is established that an intensive training results in a lower average resting heart rate. Management of bradycardia in an athlete can be difficult given the underlying mechanisms are not clearly understood. The authors reviewed the different mechanisms described in the literature, including recent advances in physiology regarding remodeling of ion channels, which may partially explain bradycardia in athletes. Sinus bradycardia amongst athletes, especially endurance focused athletes, is common but difficult to apprehend. The underlying mechanisms are observably of multifactorial origin and likely incompletely elucidated by the current body of knowledge.